Obtenção de ferrita de cobalto pelo processo de síntese e decomposição térmica de 8-hidroxiquinolinatos - Retizlaf, Alessandro (2019)
Recently, the synthesis of ferrite nanoparticles has been a reason for much study due to its electronic, optical and magnetic properties. Among the ferrites, the cobalt ferrite (CoFe2O4), which is an inverse face spinel (CFC), has several applications in many areas. Currently, there are several methodologies available in the literature to synthesize CoFe2O4 as sol-gel, coprecipitation, synthesis by thermal decomposition, polymer precursors, among others. However, depending on the methodology, it significantly interferes with the physical and chemical properties of the compound formed. Therefore, the present study aims to propose a new route of synthesis for CoFe2O4 by the thermodecomposition of precipitates simultaneously synthesized with 8-Hydroxyquinoline (8-HQ), which is a chelating agent widely used in gravimetry, due to the fact that to generate stable precipitates and with well defined stoichiometry. In this way, the work can be divided into three stages: the first is the synthesis, which was performed by mixing the metal nitrates with the 8-HQ. The pH of the reaction media was adjusted to two values (6 and 9) by addition of ammonium hydroxide (NH4OH). Subsequently, the precipitates were filtered, washed, dried and then characterized by XRD, FTIR, Raman, MEV and Colorimetry. The second step, refers to the study of the thermal behavior by TGA, DTG and DTA. In the third and last step, the precipitation was calcined at temperatures of 500, 600 and 700 ° C, as well as the characterization by DRX, Raman, Mössbauer, MEV and TEM. Based on the analyzes, it was possible to verify the precipitation of both metal chelates (Co and Fe), that the pH interferes in the morphology and crystallinity of the chelates, the thermodecomposition conditions in synthetic air do not interfere in the formation of the final product, elevation of the calcination temperature causes an increase in the crystallite size. Finally, the proposed method was highlighted as being a very promising alternative in obtaining CoFe2O4 powders.